P245 Assessment of acute illness severity and radiological extent identify patients at heightened risk of developing major pneumonic progression in influenza A H1N1/2009 infection. (16th November 2010) - Choy, J; Draper, A; Ribbons, E; Vlahos, I; Grubnic, S; Bicanic, T; Riley, P; Wansbrough-Jones, M; Chua, F
Abstract : Introduction: In 2009, high transmissibility of a novel influenza A H1N1 virus produced a global outbreak of febrile pneumonic illness. Clinical criteria for its' diagnosis suffered from low sensitivity and specificity. We evaluated clinical, laboratory and radiological abnormalities in virologically proven H1N1/2009 infection to identify risk factors associated with severe pulmonary involvement. Methods: Data were collected at one London acute care Trust during two phases (June–August and September–November 2009) of the pandemic. Initial 24-h Acute Physiology and Chronic Health Evaluation (APACHE)-II scores and radiological findings were evaluated. All data were analysed by logistic regression (STATA). Results: 64 patients (31 female, 33 male; median age 32) hospitalised with H1N1/2009 were studied, comprising 22 white British, 19 African-Caribbean, 21 Asian and 2 of other ethnicity. Only three patients were aged >60 and only two deaths were encountered. Six pregnant patients were treated, including five in phase 2. Higher mean APACHE-II scores (7.9 vs 6.6) were recorded during this phase but were unrelated to demographic factors. ICU admission rate was high (12/64 patients, 19%; including three who were pregnant). Asthma was the commonest co-morbidity (17/64 patients, 27%) but only featured in two ICU cases. By contrast, pregnancy was a predictor of ICU admission (Pearson χ 2 4.2, P 0.03). Asian males more than any other demographic were also more frequently identified than expected for this population (χ 2 4.94, p=0.026). Radiographic abnormalities were noted in ≥2 quadrants of 28 (44%) initial chest films, most frequently basal peribronchial thickening and perihilar opacities. Progressive infiltrates or multifocal consolidation were noted in 15/58 (26%) patients, two-thirds (9/15) of whom ultimately requiring intubation. Nosocomial infections or co-pathogens were found in six cases, all with underlying malignancy, transplanted organ or pregnancy. Conclusions: Most patients hospitalised with H1N1/2009 were young, with mild clinical and radiological disease. Asian males were more likely to be hospitalised with the illness, while pregnancy was correlated with an increased likelihood of ICU admission. Neither subgroup had evidence of worse acute illness severity. Basal non-lobar changes were the commonest radiographic finding. Overall, diffuse early abnormalities frequently preceded the development of severe and progressive pneumonia.